Development of a Small Rice Combine Harvester - Kalsirisilp, R; Salokhe, V.M.; Youprasobchok, C; Polwong, C; Fanchaiyapoom, E; Baisaengchanand, S; PanYawan, W (Frontiers in Engineering Innovation Research, 2009)
The objective of this research was to design, fabricate and evaluate the performance of the small rice combine harvester. This machine was designed based on the local needs especially suitable for small farm’ Presently, the Thai-made combine harvester without grain tank weights at least 5-6 tons. The total weight of the small combine was designed approximately 2.8 tons. The machine consists of harvesting unit, threshing unit, undercarriage unit and cleaning unit. A 72 hp, diesel engine was used as a power source of the machine. The cutting width of the machine was 1.8 meter. The diameter of the threshing cylinder was designed to be 360 mm with the length of 1,000 mm. The blower fan has five paddles. The peripheral speed of threshing cylinder was designed as 9.4 m/s. Performance parameters for the study were effective field capacity, field efficiency, harvesting losses, fuel consumption and the cost of harvesting.The test results indicated that the effective field capacity was 0.37 ha/h at the engine speed of 1,700 rpm.The corresponding field efficiency was 78%. The total grain losses was 5.4% of grain yield at the engine speed of 1,700 rpm. The average percent grain purity was 95%. The fuel consumption of the small combine harvester at the engine speed of 1,700 rpm was 15.5 liter/ha. The total cost of using the machine was calculated as Baht l,328/ha.